Exploring interest formation in English learning through XploreRAFE+: a gamified AR mobile app - Wang, Dan; Md Khambari, Mas Nida; Wong, Su Luan; Razali, Abu Bakar (Multidisciplinary Digital Publishing Institute, 2021)
The use of gamification and AR technology is found to have the capacity to enhance students’ interest. In this study, the researchers chose a class in a vocational college in China as a specific case that used the gamified AR mobile application, called XploreRAFE+. This study aimed to explore the use of XploreRAFE+ in the formation of learners’ interest in order to answer the research question: What is the process of interest formation among vocational college students in a gamified AR environment, and how does it sustain students’ motivation in learning English? The data for the study were collected via observations, interviews, and document analysis. The findings of the study indicated that in a gamified AR environment, vocational college students’ interest was triggered by piquing curiosity. This then led to optimal learning experiences, where eventually the students began to have positive perceptions of English lessons and were motivated to extend learning experience on their own. These three components of interest formation formed a dynamic loop where interest formation was developed in a cyclical process. It is proposed that a cyclical formation of interest developed through a gamified AR environment over time could sustain learners’ motivation.